The SNMP evolution: lost on simplicity or on functionality - Lopes, Rui Pedro (2011)
The SNMP framework has gained a new stimulus with the efficient emergence of the third version (SNMPv3). Beyond its enrichments, namely the security model, the enormous base of legacy knowledge and legacy systems leads the SNMP management framework to a necessary choice in nowadays management scenarios. However, its services correspond roughly to low-level operations for setting or retrieving network equipment parameters. Traditionally, high-level management operations were outside the scope of IETF strategy. The IETF Distributed Management working group have been producing normalization documents that intent to apply to the enrichment of SNMP semantics, especially in what concerns the processing of management information. One of such deliverables is the Expression MIB that, up till now, is in the Internet draft standard track. This paper will highlight the recent outcome of this WG, will present an Expression MIB implementation and will discuss the cost of these more powerful solutions on the “keep simple” and “low inference” principles of SNMP engines.